Characterization of Campylobacter fetus adherence, invasiveness, and ultrastructural damage on bovine oviductal cells - Cagnoli, Claudia Inés; Chiapparrone, María Laura; Acuña, Francisco; Cacciato, Claudio Santiago; Rodríguez, Marcelo Gastón; Aller Atucha, Juan Florencio; Catena, María del Carmen (Elsevier, 2025)
Bovine campylobacteriosis is a distributed worldwide disease caused by Campylobacter fetus. It is a sexual transmitted disease that affects reproductive health in cattle. The objective of this study was to use bovine oviduct primary cell cultures as a pathogenicity model to study the virulence of Campylobacter fetus fetus and Campylobacter fetus venerealis. Both subspecies showed the ability to adhere to, invade and cause cytopathogenic effect in oviductal cells. Transmission electron microscopy revealed significant ultrastructural damage, including cytoplasmic vacuolization, nuclear condensation and mitochondrial alterations. These mitochondrial changes, such enlargement and fragmentation, suggest potential impacts on cell viability and host cellular metabolism. This study is the first to investigate the pathogenicity of both subspecies in primary bovine oviductal epithelial cells. These findings demonstrate the virulence mechanism of C. fetus in the reproductive tract, providing insights into oviductal pathogenicity and potential impacts on bovine fertility.